FREQUENCY OF HYPOTHYROIDISM IN MULTI-TRANSFUSED IRON OVERLOADED Î²-THALASSEMIA SYNDROME PATIENTS - Kamran, Maria (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Background: Beta thalassemia syndromes are heterogeneous inherited disorders. They represent the commonest inherited hemoglobinopathies and constitute a com-mon public health problem. Patients suffering from these disorders ultimately devel-op complications including endocrinopathies secondary to transfusional iron over-load. Thyroid dysfunction is well documented in this context; however there is great disparity in its prevalence across the world. This study was designed to determine the frequency of thyroid dysfunction in multi-transfused (> 12 regular transfusions) beta thalassemia syndrome patients in District Peshawar Pakistan. Methodology: In this cross-sectional descriptive study, patients treated at Fatimid Foundation Peshawar were enrolled. One hundred and fifteen multi-transfused beta thalassemia syndrome patients >10 years of age were included. Data and blood samples were collected after taking written informed consent from patients/guardians. Venous blood (3ml) was collected in vacuette® (Griener, GmbH). After centrifugation, sera were separated and analyzed for T4, T3, TSH and ferritin levels by Chemiluminescence Immune Assay (CLIA) technique using Acculite Monobind Diagnostics on Lumax analyzer in IBMS. Results: Primary subclinical hypothyroidism was detected in 25 (21.7%) pa-tients. All patients were iron overloaded as indicated by very high serum ferri-tin levels (ranging from 1500-27042ng/ml). Conclusion: Hypothyroidism occurs mainly in subclinical state and is a fre-quent complication in iron overloaded beta thalassemia syndrome patients with risk of progression.